Pneumococcal sternoclavicular septic arthritis: A rare manifestation of invasive pneumococcal disease - Yongdeok Shin; Seth Conley; Awol Ali; Andrew Mangano (IDCases)
Septic arthritis of the sternoclavicular joint comprises less than 1 % of all septic arthritis cases. While Streptococcus species are common causative organisms, Streptococcus pneumoniae rarely causes this infection. We present a case of pneumococcal sternoclavicular septic arthritis in a 58-year-old male with a history of alcohol use disorder and no prior pneumococcal vaccination. Despite the introduction of pneumococcal vaccines, unvaccinated individuals remain at risk, especially those with comorbidities. This case highlights the need for vaccination and early intervention in high-risk populations.